KAJIAN NILAI PENDIDIKAN RELIGIUS DALAM TRADISI NGELAWANG BARONG BANGKUNG - Ni Wayan Ria Lestari; Ni Nengah Sudarsini (Institut Agama Hindu Negeri Gde Pudja Mataram, 2024)
The Ngelawang Barong Bangkung tradition is an activity carried out by sekaa or a group of people to dance the barong benchung from one house door to another during the celebration of the holy days of Galungan and Kuningan. The formulation of the problem in this research is regarding the philosophical Ngelawang Barong Bangkung in Kediri Village, Kediri District, Tabanan Regency and the religious educational values ​​contained in the Ngelawang Barong Bangkung procession. The theories used in this research are symbolic interactionism theory and religious theory. The type of data for this research is descriptive qualitative. The informants were determined using purposive sampling. The data in this research was obtained through: observation, interviews, documentation. The results obtained include: 1) Philosophically, the Ngelawang Barong Bangkung tradition in Banjar Dinas Pande and Banjar Dinas Demung, Kediri Village is a sacred tradition that has existed for a long time and has been passed down from generation to generation and is still carried out to this day. The community believes that there is a spirit that animates the implementation of the ngelawang barong benchung tradition. The barong benchung in these two banjars is believed to be a manifestation of Ida Sang Hyang Widhi Wasa. 2) The religious education values ​​contained in the Ngelawang Barong Bangkung procession in Kediri Village, Kediri District, Tabanan Regency consist of: a. aspects of religious belief, b. aspects of worship (religious practice), c. aspects of appreciation (religious feeling) d. knowledge aspect (religious knowledge), e. practice aspect (religious effect).